Cross-media: estudo comparativo da lembrança de propaganda em tv e streaming - Carletti , Rafael Ribeiro (2024)
The goal of this study is to comparatively analyze the recall rate of advertisements delivered via TV and Streaming Video. The Brazilian market underwent a transformation from the 2020s onwards, as audiences moved away from traditional TV channels and migrated to digital platforms such as YouTube and Netflix. Aware of this movement, advertising agencies emphasized cross-media strategies, distributing ads in more than one medium to maximize reach on the target audience. However, there is no comparative analysis of the recall of video ads on TV in relation to Streaming. In addition to this comparison, this work aims to study the moderating effect of the frequency of ad exposure on recall across different platforms. The methodological approach is based on field experiments simulating ad exposure on TV and Streaming, at different frequencies, to compare media efficiency.